Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Terhadap Produk Rabbani di Bunker Rabbani Pucang Surabaya - Mariska Pradnya Paramitha; Fatin Fadhilah Hasib (Universitas Airlangga, 2014)
This research aims to identify factors affecting consumer buyer decision to buy Rabbani products in Bunker Rabbani Pucang Branch Surabaya, amid burgeoning hijab trend fashion and competitive pressure from other retailers of moslem clothing products. In our study we employed quantitative approach, which followed by analysis using exploratory analysis factor. The sample population that we studied comprised of female customers buying Rabbani products in the above retailer, which we surveyed by using simple random sampling. The primary data collection is conducted in two stages: pre-test and main test, whereas secondary data are obtained elsewhere from literature. The pre-test was carried out by posing the questionnaire to 30 respondents. The result of pre-test is subsequently used as instrument indicator for main test which involving 91 respondents. From our investigation we obtained three factors behind consumer buyer decision to buy Rabbani products in the store used as case study: factor of product types, factor of price and store location, and factor of store promotion. Based on this result we thus provide suggestion to Rabbani store to keep up product attribute existence amid burgeoning hijab trend fashion and competitive pressure from other retailers of moslem clothing products. REFERENCESAl-Quran dan Terjemahnya. 1998. Semarang: Asy Syifa’.Burhani, Ruslan. 2012, Perkembangan Fesyen Muslimah Menggembirakan. Gaya Hidup, Antara News. (Online), (http://www.antaranews.com//, diakses 15 April 2013).Dartistiana, Nabiya Carissa. 2013. Faktor yang Mempengaruhi Keputusan Mahasiswa Memilih Program Studi S1 Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga. Skripsi tidak diterbitkan. Fakultas Ekonomi dan Bisnis Universitas Airlangga.Dessyana, Cindy J. 2013. Store Atmosphere Pengaruhnya Terhadap Keputusan Pembelian Konsumen Di Texas Chicken Multimart II Manado (Online), Volume 1 Nomor 3, (http://ejournal.unsrat.ac.id//, diakses 1 Oktober 2013).Hidayat, Asep Taufik. 2012. Hubungan Antara Atribut Produk dengan Minat Beli Konsumen (Online), Volume 1 Nomor 1, (http://jurnal.unpad.ac.id//, diakses 20 Desember 2013).Malhotra, Naresh K. 2009. Riset Pemasaran Pendekatan Terapan Edisi Keempat Jilid Satu. Jakarta: PT Indeks.Muflih, Muhammad. 2006. Perilaku Konsumen dalam Perspektif Ilmu Ekonomi Islam. Jakarta: Raja Grafindo Persada.Palmer, Adrian. 2012. Introduction to Marketing Theory and Practice. Oxford: Oxford University Press.Rizan, Mohammad dkk. 2012. Pengaruh Brand Image dan Brand Trust Terhadap Brand Loyalty The Botol Sosro (Online), Volume 3 Nomor 1, (http://www.jrmsi.com//, diakses 1 Oktober 2013).Santoso, Singgih. 2010. Statistik Multivariat. Jakarta: PT Elex Media Kumputindo.Schiffman, L.G. and L.L. Kanuk. 2004. Consumer Behavior. New Jersey : Pearson Prentice Hall.Sebayang, Muly Kata dan Simon Darman O. Siahaan. 2008. Pengaruh Celebrity Endorsesr Terhadap Keputusan Pembelian Sepeda Motor Merek Yamaha Mio pada Mio Automatic Club (MAC) Medan (Online), Volume 1 Nomor 3, (http://usupress.usu.ac.id//, diakses 28 September 2013).Tjiptono, Fandy. 1997. Strategi Pemasaran. Yogyakarta: Penerbit Andi.———-, 2005. Pemasaran Jasa. Malang: Bayumedia.Velany, Aisyah. 2008. Pengaruh Cause Related Markering (CRM) Terhadap Loyalitas Pelanggan Air Minum Dalam Kemasan (AMDK) Merek Aqua pada Mahasiswa Sarjana Reguler Universitas Indonesia. Tesis tidak diterbitkan. Fakultas Ilmu Sosial dan Ilmu Politik Universitas Indonesia.Widagdo, Herry. 2011. Analisis Pengaruh Kualitas Layanan dan Promosi Terhadap Keputusan Konsumen Membeli Komputer pada PT XYZ Palembang (Online), Volume 1 Nomor 1 , (http://eprints.mdp.ac.id//, diakses 29 September 2013).Wulandari, Wahju. 2012. Pengaruh Marketing Mix Terhadap Keputusan Pembelian Pada Waserda UKM Mart Koperasi Karyawan Widyagama Malang (Online). Volume 1 Nomor 3, (http://widyagama.ac.id/ejournal/ /, diakses 1 Oktober 2013).Yusrizal. 2008. Pengujian Validitas Konstruk dengan Menggunakan Analisis Faktor ( Online), Volume 5 Nomor 1, (http://digilib.unimed.ac.id//, diakses 27 September 2013).